1998
DOI: 10.1159/000010016
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase in Thrombin Generation during Radiotherapy of Uterine Carcinoma: A Preliminary Study using Thrombin-Antithrombin III Complex Measurements

Abstract: The question of the study was whether irradiation therapy applied to women with cervical or endometrial carcinoma leads to increased thrombin generation. The study group consisted of 42 women with cervical carcinoma (22 cases) and endometrial carcinoma (20 cases). Irradiation (brachytherapy or/and teletherapy) was applied as follows: 200 cGy/day, 5 days a week, therapeutic dose of 4,500–5,000 cGy. Complexes of thrombin-antithrombin III in blood plasma were measured (ELISA method) before radiotherapy and 4–5 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…35 In addition, Uszýnski et al showed a transient increase in TAT in 20% of patients during radiotherapy, but no significant difference was found before and after radiotherapy when compared to healthy controls in a study of 46 patients with stage I-IV cervical or endometrial cancer treated with adjuvant or definitive radiotherapy. 36 Sierko et al reported no significant differences in TAT throughout the treatment course in a prospective study of 16 patients with stage IIB-IVa head and neck cancer receiving definitive radiotherapy, post-operative radiotherapy, or chemoradiotherapy. 37 The findings of Uszýnski et al and Lincz et al suggest that radiotherapy might induce increased in vivo thrombin generation.…”
Section: Discussionmentioning
confidence: 96%
“…35 In addition, Uszýnski et al showed a transient increase in TAT in 20% of patients during radiotherapy, but no significant difference was found before and after radiotherapy when compared to healthy controls in a study of 46 patients with stage I-IV cervical or endometrial cancer treated with adjuvant or definitive radiotherapy. 36 Sierko et al reported no significant differences in TAT throughout the treatment course in a prospective study of 16 patients with stage IIB-IVa head and neck cancer receiving definitive radiotherapy, post-operative radiotherapy, or chemoradiotherapy. 37 The findings of Uszýnski et al and Lincz et al suggest that radiotherapy might induce increased in vivo thrombin generation.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, recent evidence concluded that therapeutic doses of ionic energy caused a transient increase in thrombin generation during radiotherapy. 64 As combined antiangiogenic/radiotherapy treatments are already underway as Clinical Phase I trials in adult patients, we propose that the cooperative anti-tumoral effects of naturally occurring green tea polyphenols possessing anti-angiogenic properties combined with irradiation treatments will help optimize the present clinical treatments. The synergistic effects obtained when radiotherapy is combined with low-dose metronomic anti-angiogenic therapy should thus provide the underpinnings for the development of new therapeutic strategies using a nutraceutical approach.…”
Section: Discussionmentioning
confidence: 99%